(untitled) (Journal of Oriental Studies, 2021)
This presentation focuses on the lost and uncertainty of meaning in Yesevi wisdom tradition despite its enlargement in a wide geography and representatives belong to it. Within this frame, the presentation asserts that after the loss of the place and appliers of the tradition, the meaning is lost consequently. Because the methods applied on obtaining the meaning is based on the practice, it is being possible to transfer the data to receiver by implementer by means of the place. In fact, the mind of the receiver and spiritual world transmit into the paper, on which knowledge and aphorism is written. Thus, the meaning, which the place and message get at the same time, makes visible the receiver which is the appearance place of “being”. Besides, the other area in which this activity is happened is “meeting place”, i.e. universe (alem). This study will mention on of the basic principles of Yesevi wisdom, Meal (Sofra) via some conceptualizations such as place, kevn, universe, book, page, volume, etc. Holding the meal (sofra tutmak) is Yesevi wisdom means the assignment of the caliph, who was grown up by his own sage (pir). So, the receiver finished his growing up process get his task, in which he was assigned, is given this task by the following order: “Hold the Meal”. As an assign of maturity, meal is among the six deposits given to receiver. Meal (sofra) is coming from the same root of the word voyage (sefer). Accordingly, it keeps the meaning of cover and journey. Giving the task as the beginning of the journey or the obtained meaning of the covering the human’s being are shaped around Surah Insan in Qur’an. Holding the meal is necessary for atonic people, orphans, and slaves. Opening the meal means opening the cover on atonic people, orphans, and slaves. Consequently, one of the important subjects for loss Yesevi wisdom is holding the meal. Presentation proposes to remind people of their journey, which is the first task for Turkish-Islamic Guild (Fütüvvet) for Allah, which they fall behind, on the other hand, it proposes to remove the cover that hide the reality on the people. This point is clearly explained both in the Surah Insan and Maide. Key words: Yesevi wisdom, traditions, Holding the meal, Surah Insan, Surah Maidе.